VD_FINDINFO ML / 2010 / 184 vom 17. Oktober 2005 - VD Tribunal cantonal (2005)
MAINLEVÉE DÉFINITIVE, BAIL À LOYER, MONNAIE ÉTRANGÈRE, COURS DE CONVERSION | 25 CL, 31 al. 1 CL, 36 CL, 38 CL, 40 ch. 2 CL, 67 al. 1 ch. 3 LP, 69 LP, 80 LP, 81 LP, 58 al. 4 LVLP